2013
DOI: 10.1002/biof.1133
|View full text |Cite
|
Sign up to set email alerts
|

Berberine acts as a natural inhibitor of Wnt/β‐catenin signaling—Identification of more active 13‐arylalkyl derivatives

Abstract: Aberrant activation of the canonical Wnt/β-catenin signaling pathway has been reported for numerous tumors of different origins. In most cases, mutations in components of the Wnt signaling pathway or in β-catenin itself were detected which ultimately induce a genetic program that promotes cell proliferation and attenuates apoptosis. Thus, targeting of Wnt/β-catenin signaling is of specific therapeutic interest. Herein, we investigated the plant-derived isoquinoline alkaloid berberine, which has been reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 44 publications
1
36
0
1
Order By: Relevance
“…We describe here for the first time that the BBR derivatives NAX012, 14, and 18 affect cell cycle distribution in a p53 -dependent manner, in agreement with published data for the lead compound BBR [7, 4042]. …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…We describe here for the first time that the BBR derivatives NAX012, 14, and 18 affect cell cycle distribution in a p53 -dependent manner, in agreement with published data for the lead compound BBR [7, 4042]. …”
Section: Resultssupporting
confidence: 88%
“…These observations are in line with previous reports showing that BBR itself promotes the activation of procaspase 9 and mitochondria deregulation, typically observed in the intrinsic subroutine of apoptosis [19], although in some experimental systems BBR proved to activate the extrinsic pathway [46, 47]. The proapoptotic effect of BBR on cancer cells was reported to be associated with the modulation of JNK/p38-redox/ROS process, HER2/PI3K/AKT signaling, p53 -regulated factors and NF- κ B, AP-1, Wnt, and COX-2 proteins [3, 7, 22, 40, 42]. …”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that berberine blocks Wnt/β-catenin signalling, inhibits cell migration (Park et al, 2012;Albring et al, 2013) and has the ability to regulate cell attachment through zonula occludens 1 protein (ZO-1) (Liu et al, 2009). Berberine can activate ZO-1, helps in the formation of tight junctions between cells and reduces cell mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Phytic acid is a product of rice bran known to inhibit β-catenin during AOM-induced colon cancer (Saad et al, 2013;Shafie et al, 2013). Berberine acts as a natural inhibitor of Wnt/β-catenin signaling in HCT-116 colon carcinoma cells (Albring et al, 2013). The antiproliferative and antitumor activities of 2-hydroxycinnamaldehyde (1), a phenylpropanoid isolated from the bark of Cinnamomum cassia was found to inhibit β-catenin/T-cell factor (TCF) transcriptional activity in HCT116 colon cancer cell line .…”
Section: Wnt/β-catenin Signaling and Colon Cancermentioning
confidence: 99%